Turkey's Energy Security Strategy in the Emergent Global Energy Outlook - Guney, Nursin Atesoglu (SETA FOUNDATION, 2015)
Since the beginning of the 2000s the global energy landscape has undergone constant change. Various factors have affected both the demand and supply sides of the global energy security outlook. As a result, both consumer and producer states have constantly felt the need to adapt to emergent market conditions. Hence, this paper first aims to highlight the continuous changes within the global energy market and simultaneously present and evaluate Turkey's determined search to fulfill the requirements of its energy supply security strategy.
Keywords: Government & Law